Oxynoemacheilus hazarensis, a new species from Lake Hazar in Turkey, with remarks on O. euphraticus (Teleostei: Nemacheilidae) - Freyhof, Jörg; Özuluğ, Müfi̇t (Zootaxa, 2017)
Oxynoemacheilus hazarensis, new species, from Lake Hazar in the Turkish Tigris drainage, is distinguished from other Oxynoemacheilus in the Tigris drainage by having the combination of a slightly emarginate caudal fin, no suborbital groove in males, an incomplete lateral line, no scales on the back and flank in front of the anus, the maxillary barbel reaching beyond the middle of the eye, an incision in the middle of the upper lip, and the colour pattern on the flank mottled, not interrupted by an unpigmented zone along the lateral line. Oxynoemacheilus euphraticus from the Euphrates and Tigris drainages is a valid species: it is discussed and re-diagnosed against O. argyrogramma.